MOTIVASI KERJA PEGAWAI DI PT. FIRMAN MULYA JAYA KOTA MAKASSAR - Ishak, Rasdiana; Madani, Muhlis; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This research aims to determine employee work motivation at PT. Firman Mulya Jaya Makassar City. This type of research uses qualitative methods with a case study approach research type, data collection techniques through observation, interviews and documentation. The research results show that employee work motivation at PT. Firman Mulya Jaya Makassar City has attempted to meet needs based on work motivation indicators according to Abraham Maslow, (1) Physiological needs, companies have not fully met these needs with various policies. (2) The need for security, the company meets employee needs by providing work safety equipment, health benefits and old age security. (3) Social needs or a sense of belonging through strong teamwork in a work environment that involves teamwork. (4) The need for appreciation has also been fulfilled through recognition and appreciation. (5) The need for employee self-actualization is reflected through a proactive attitude in finding new solutions.